HASIL BELAJAR MATA PELAJARAN CNC MENGGUNAKAN MEDIA SIMULASI SWANSOFT CNC PADA PESERTA DIDIK SMK NEGERI 1 MAGELANG - Panuntun, Ginanjar Bagus (Journal of Mechanical Engineering Learning, 2014)
Swansoft CNC simulation media is a complete simulation media which is the same as the real CNC machine. The purposes of this study were to determine the learning outcomes before and after treatment, an increase in the experimental class and comparison with the control class. The researcher used pre-test and post-test control group design . The sample itself is taken is taken in TMC class as a control group, and TMD class as an experimental group. The results showed the average post-test learning outcomes t_count = 3,763 < t_ table = 1.68. Because t is in the region of rejection of Ho, therefore, the experimental group was higher than the control group. The average of pre-test learning outcomes of experimental group was 64,60 and the control group 64,23. The average of post-test learning outcomes experimental class was 84.20, meanwhile the control class 77.31 . The researcher concludes that 1 ) The average of pre-test learning outcomes are relatively similar in both groups and low categorized; 2 ) The average of post-test learning outcomes experimental class was 84,20, meanwhile the control class 77.31 ; 3) Both groups is significantly increased ; 4 ) The results of the experimental class learning is better than control class. It is suggested for the teachers to use Swansoft CNC simulation media. For the further research, investigating the psychomotor as well also needed.